ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWANPADAKLINIK GIGI WIJAYA DI CIKARANG UTARA, KABUPATEN BEKASI - Zubastian Rachman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effect of the work environment on employee performance at WijayaDental Clinic in North Cikarang, Bekasi Regency. The work environment consisting of physical, social, and psychological aspects is recognized as a key determinant of motivationandproductivity. Employing a quantitative associative causal research design with a saturatedsampling technique (N=50), this study utilizes simple linear regression, t-test, andthecoefficient of determination to analyze the data. The findings demonstrate that theworkenvironment has a Keywords : Job Creation Law, Industrial Relations, Termination of Employment (PHK), Juridical Correction, Worker Protection.